The use of Agrochemicals for inc BIOAVAILABILITY OF HEAVY METALS Pb AND Cd IN LAND FOR CULTIVATYING CABBAGE IN KINTAMANI AREA BANGLI - mahendra, regi; Siaka, I Made; Suprihatin, Iryanti Eka (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 12 No 1 (2018)DO - 10.24843/EJES.2018.v12.i01.p06, 2018)
The use of Agrochemicals for increasing the agricultural products are commonly applied on agricultural soils, especially the soil used for cultivatif cabbage in the area of Kintamani-Bangli, Province of Bali. Agricultural soils used for cultivatif cabbage in Kintamani area commonly apply inorganic fertilizers and synthetic pesticides for increasing the products. However the use of these agrochemicals tends to uncontrol and causes the soils polluted. One factor of contamination of soil is the presence of heavy metals in the soil. Intensive use of inorganic fertilizers and synthetic pesticides can lead to high levels of bioavailability of heavy metals in plants. This study intend to determine the total contents of heavy metals Pb and Cd in the agricultural soils and analyse bioavilability of those metals. The total metals was determined by the use of digestion method involving reverse aquaregia (HNO 3 :HCl, 3:1)  and the bioavailability of the metals was determined by applying single extraction including HCl and EDTA extractions. The results show that the total contents of Pb and Cd in the soils were 4,1261 ± 0,1113 – 14,5923 ± 0,3790 mg/kg and 0,8803 ± 0,0259 - 0,9425 ± 0,0195 mg/kg respectively. The bioavailable metals of Pb and Cd in the soils was 31,14% - 42,53% and 78,70% - 80,73%, respectively.